Facing Scarcity in a Land Grab Context in Cameroon - Hugues Morell Meliki (Swiss Journal of Sociocultural Anthropology, 2021)
This paper undertakes a critical exploration of the mechanisms via which communities cope with scarcity resulting from land grabs. It explores two ranges of practices – residential multilocality and sorcery – through the lens of resilience. Residential multilocality appears as a novel living arrangement dealing with resource scarcity, while sorcery is used as a tool for bolstering a policy of resource regeneration. Thus, instead of rushing to nearby cities as a response to scarcity, the communities observed reinstate two silenced dynamics. Firstly, they underscore the rise of inter, and intra-rural mobility entrenched in the paradigm of residential multilocality. The paradigm embodies a scarcity management strategy in the sense that the abundance of vital resources in one rural area attracts villagers from other communities struggling with scarcity. Secondly, sorcery is used as a strategy to command eco-friendly behavior of villagers in order to successfully achieve a resource regeneration policy.